How Will Climate Change Affect the Provision and Value of Water from Public Lands in Southern California Through the 21st Century?. (April 2020) - Srivastava, Lorie; Hand, Michael; Kim, John; Sánchez, José J.; Lupi, Frank; Garnache, Cloé; Drapek, Raymond J.; Quinn, James F.
Abstract: We estimate the ecosystem service value of water supplied by the San Bernardino National Forest in Southern California under climate change projections through the 21 st century. We couple water flow projections from a dynamic vegetation model with an economic demand model for residential water originating from the San Bernardino National Forest. Application of the method demonstrates how estimates of consumer welfare changes due to variation in water supply from public lands in Southern California can inform policy and land management decisions. Results suggest variations in welfare changes over time due to alterations in the projected water supply surpluses, shifting demand limited by water supply shortages or surpluses, and price increases. Results are sensitive to future climate projections—in some cases large decreases in welfare due to supply shortages—and to assumptions about the demand model.